Determination of Employee Performance: An Empirical Study of the Influence of Motivation and Competence with Performance Allowance as a Moderator - Ratna Mufidah; Sarwo Edy Handoyo; Andi Harmoko Arifin (JURNAL ILMIAH GEMA PERENCANA, 2026)
This study aims to analyze the determinants of employee performance at the Ministry of Religious Affairs Office in Jembrana Regency through the influence of motivation and competence, with performance allowances as a moderating variable. This study is motivated by the decline in the ASN Professionalism Index (IP) from 82.99 (2023) to 78.38 (2024), as well as the dynamics of online attendance discipline and functional competency gaps. Data were processed using a quantitative method with a Structural Equation Modeling - Partial Least Square (SEM-PLS) analysis approach using a causal associative design with the population analysis unit and the research sample being all State Civil Apparatus employees (PNS and PPPK) at the Ministry of Religious Affairs Office in Jembrana Regency, totaling 80 respondents, using a saturated/census sampling technique. The results showed that motivation had a positive and significant effect on employee performance (t-statistic 2.450; p < 0.05). Competence was also shown to have a positive and significant effect on performance (t-statistic 2.684; p < 0.05). A crucial finding of this study is that performance allowances were shown to positively and significantly moderate the effect of motivation on performance (t-statistic 1.980; p < 0.05) and moderate the effect of competence on performance (t-statistic 1.974; p < 0.05). The R-square value of 0.682 indicates that this research model is able to explain 68.2% of employee performance variance, providing strategic implications for strengthening the meritocracy-based human resource management system within the Ministry of Religious Affairs.